Performance and Impacts of Public Policies on Environmental Sustainability? Debating the portuguese case of the PO SEUR 2014-2020 - Medeiros, E.; Valente, B.; Castro, P.; Gonçalves, V. (Third Joint EU Cohesion Policy Conference, 2022)
Sustainable development is a key feature of national, European Union and Global development strategies. The main research goal is to provide evidence on how impactful public policies on environmental sustainability in Portugal at the regional level, in various policy areas. In this context, this paper analyses the main impacts of the Portuguese Operational Programme for Sustainability and Efficient Use of Resources (PO SEUR 201420). The research uses a territorial impact assessment (TIA) methodology (TARGET_TIA) to assess these impacts in five analytic dimensions (economy with low emissions, adaptation to climate change, risk prevention and management, environmental protection and resource efficiency) in the five mainland Portuguese NUTS II. Three main conclusions emerge from the analysis: Firstly, despite all the challenges related to lack of data at the regional level, the used methodology enables us to obtain a detailed as possible impact assessment analysis. The main reason for that was the methodological possibility to use a ‘regional sensibility’ approach to identify the policy investment needs of the analysed regions in the analysed five policy dimensions. In addition, a ‘policy intensity’ analysis of the PO SEUR investments in all these dimensions per region added to the precision of the impact analysis. Finally, statistical data was used to verify potential causalities of the PO SEUR on these five policy domains at the regional level. The use of all these elements contributed to finetune the impact scores obtained via 30 interviews to local, regional, intermunicipal and national stakeholders. Secondly, the obtained results should be read with care. More concretely, comparable regional statistics on environmental sustainability did not permit a solid causality analysis. On the other hand, the qualitative data obtained during the interviews was not sufficiently robust to perform a counterfactual analysis of the evaluation. Finally, several interviewees are interested parts in the PO SEUR which can influence their statements. Even so, the collected data is sufficiently robust to validate the obtained impact scores in each region and analytical dimension. In essence, further research on the impacts of the PO SEUR should incorporate a large number of interviews with the inclusion of academic experts, which was not possible in this analysis. Thirdly, and based on the previous statements, the analysis concluded that the PO SEUR had an overall low to moderate positive impact on environmental sustainability in mainland Portugal during the 20142020 period. The highest positive impacts were registered in the ‘adaptation to climate change dimension’, and the least positive in the ‘economy with lower emissions’ and ‘resource efficiency’ dimensions, despite the fact that the latter received the bulk of the PO SEUR’ investment. From a regional perspective, the Norte NUT 2 presented more positive impact scores than the remaining mainland NUTS 2, and the Alentejo region presented the less positive impact scores. It is also possible to conclude that the impacts of the PO SEUR in all five analytical dimensions varied significantly from region to region. Even so, the ‘economy with low emissions’ had quite low positive impact scores in all regions. This demonstrates that the EU policy goal towards a transition to a green economy in Portugal is not being sufficiently supported via existing policy instruments to finance environmental sustainability’ projects. In this stance, in our view, a higher policy strategic policy emphasis should be placed in financing ‘green economy’ related projects in all Portuguese regions in future environmental sustainability programmes.